Ontogenetic Development of Weberian Ossicles and Hearing Abilities in the African Bullhead Catfish - Lechner, Walter (Public Library of Science, 2011)
BACKGROUND: The Weberian apparatus of otophysine fishes facilitates sound transmission from the swimbladder to the inner ear to increase hearing sensitivity. It has been of great interest to biologists since the 19(th) century. No studies, however, are available on the development of the Weberian ossicles and its effect on the development of hearing in catfishes. METHODOLOGY/PRINCIPAL FINDINGS: We investigated the development of the Weberian apparatus and auditory sensitivity in the catfish Lophiobagrus cyclurus. Specimens from 11.3 mm to 85.5 mm in standard length were studied. Morphology was assessed using sectioning, histology, and X-ray computed tomography, along with 3D reconstruction. Hearing thresholds were measured utilizing the auditory evoked potentials recording technique. Weberian ossicles and interossicular ligaments were fully developed in all stages investigated except in the smallest size group. In the smallest catfish, the intercalarium and the interossicular ligaments were still missing and the tripus was not yet fully developed. Smallest juveniles revealed lowest auditory sensitivity and were unable to detect frequencies higher than 2 or 3 kHz; sensitivity increased in larger specimens by up to 40 dB, and frequency detection up to 6 kHz. In the size groups capable of perceiving frequencies up to 6 kHz, larger individuals had better hearing abilities at low frequencies (0.05–2 kHz), whereas smaller individuals showed better hearing at the highest frequencies (4–6 kHz). CONCLUSIONS/SIGNIFICANCE: Our data indicate that the ability of otophysine fish to detect sounds at low levels and high frequencies largely depends on the development of the Weberian apparatus. A significant increase in auditory sensitivity was observed as soon as all Weberian ossicles and interossicular ligaments are present and the chain for transmitting sounds from the swimbladder to the inner ear is complete. This contrasts with findings in another otophysine, the zebrafish, where no threshold changes have been observed.